Gestational VPA exposure reduces the density of juxtapositions between TH+ axons and calretinin or calbindin expressing cells in the ventrobasal forebrain of neonatal mice - Finszter, Cintia Klaudia; Kemecsei, Róbert; Zachar, Gergely; Ádám, Ágota; Csillag, András (Frontiers in Neuroanatomy, 2024)
Gestational exposure to valproic acid (VPA) is a valid rodent model of human autism spectrum disorder (ASD). VPA treatment is known to bring about specific behavioral deficits of sociability, matching similar alterations in human autism. Previous quantitative morphometric studies from our laboratory showed a marked reduction and defasciculation of the mesotelencephalic dopaminergic pathway of VPA treated mice, along with a decrease in tissue dopamine in the nucleus accumbens (NAc), but not in the caudatoputamen (CPu). In the present study, the correlative distribution of tyrosine hydroxylase positive (TH+) putative axon terminals, presynaptic to the target neurons containing calretinin (CR) or calbindin (CB), was assessed using double fluorescent immunocytochemistry and confocal laser microscopy in two dopamine recipient forebrain regions, NAc and olfactory tubercle (OT) of neonatal mice (mothers injected with VPA on ED13.5, pups investigated on PD7). Representative image stacks were volumetrically analyzed for spatial proximity and abundance of presynaptic (TH+) and postsynaptic (CR+, CB+) structures with the help of an Imaris (Bitplane) software. In VPA mice, TH/CR juxtapositions were reduced in the NAc, whereas the TH/CB juxtapositions were impoverished in OT. Volume ratios of CR+ and CB+ elements remained unchanged in NAc, whereas that of CB+ was markedly reduced in OT; here the abundance of TH+ axons was also diminished. CR and CB were found to partially colocalize with TH in the VTA and SN. In VPA exposed mice, the abundance of CR+ (but not CB+) perikarya increased both in VTA and SN, however, this upregulation was not mirrored by an increase of the number of CR+/TH+ double labeled cells. The observed reduction of total CB (but not of CB+ perikarya) in the OT of VPA exposed animals signifies a diminished probability of synaptic contacts with afferent TH+ axons, presumably by reducing the available synaptic surface. Altered dopaminergic input to ventrobasal forebrain targets during late embryonic development will likely perturb the development and consolidation of neural and synaptic architecture, resulting in lasting changes of the neuronal patterning (detected here as reduced synaptic input to dopaminoceptive interneurons) in ventrobasal forebrain regions specifically involved in motivation and reward.